Navigating Hemorrhagic Shock: Biomarkers, Therapies, and Challenges in Clinical Care - Kenneth Meza Monge; Caleb Rosa; Christopher Sublette; Akshay Pratap; Elizabeth J. Kovacs; Juan-Pablo Idrovo (Biomedicines)
Hemorrhagic shock remains a leading cause of preventable death worldwide, with mortality patterns varying significantly based on injury mechanisms and severity. This comprehensive review examines the complex pathophysiology of hemorrhagic shock, focusing on the temporal evolution of inflammatory responses, biomarker utility, and evidence-based therapeutic interventions. The inflammatory cascade progresses through distinct phases, beginning with tissue injury and endothelial activation, followed by a systemic inflammatory response that can transition to devastating immunosuppression. Recent advances have revealed pattern-specific responses between penetrating and blunt trauma, necessitating tailored therapeutic approaches. While damage control resuscitation principles and balanced blood product administration have improved outcomes, many molecular targeted therapies remain investigational. Current evidence supports early hemorrhage control, appropriate blood product ratios, and time-sensitive interventions like tranexamic acid administration. However, challenges persist in biomarker validation, therapeutic timing, and implementation of personalized treatment strategies. Future directions include developing precision medicine approaches, real-time monitoring systems, and novel therapeutic modalities while addressing practical implementation barriers across different healthcare settings. Success in hemorrhagic shock management increasingly depends on integrating multiple interventions across different time points while maintaining focus on patient-centered outcomes.